2014
DOI: 10.1111/jfbc.12096
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor and Immunomodulatory Activity of P leurotus eryngii Extract

Abstract: Pleurotus eryngii (P. eryngii), also known as the king oyster mushroom, contains many bioactive substances, including polysaccharides, lipids, peptides, sterols and triterpenoids. The aim of this study was to explore the antitumor and immunomodulatory activities of P. eryngii extract. The fresh P. eryngii material was extracted with MeOH (methanol) and then partitioned with EtOAc (ethyl acetate). The study showed that the P. eryngii EtOAc extract (EAe) not only has antitumor effects by in vitro and in vivo met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
4
0
4
Order By: Relevance
“…Pleurotus eryngii , also known as king oyster mushroom, is commonly consumed as an edible mushroom around the world with multiple nutrition functional activities including antitumor (Xue et al., 2015), antioxidant (Choi, Kim, Kim, & Kim, 2017), antihypertensive (Khan & Tania, 2012), antimicrobial (Adebayo et al., 2018), immunomodulatory (Corrêa, Brugnari, Bracht, Peralta, & Ferreira, 2016), and anti‐inflammatory activities (Lin et al., 2014) among others. Its activities have been proven to be related to the abundance and diversity of active components.…”
Section: Introductionmentioning
confidence: 99%
“…Pleurotus eryngii , also known as king oyster mushroom, is commonly consumed as an edible mushroom around the world with multiple nutrition functional activities including antitumor (Xue et al., 2015), antioxidant (Choi, Kim, Kim, & Kim, 2017), antihypertensive (Khan & Tania, 2012), antimicrobial (Adebayo et al., 2018), immunomodulatory (Corrêa, Brugnari, Bracht, Peralta, & Ferreira, 2016), and anti‐inflammatory activities (Lin et al., 2014) among others. Its activities have been proven to be related to the abundance and diversity of active components.…”
Section: Introductionmentioning
confidence: 99%
“…Although Z-Spe could efficiently remove phospholipid interferents, it produced excessive adsorption of 53 pesticides. In onion, apricot mushroom, and pakchoi samples, small-molecule components mainly include organic acids, amino acids, vitamins, sugars, phenolic compounds, and pigments. In addition, polyphenols and alkaloids are special interferents in tea samples. , Based on the above-mentioned consideration, a mixture of PSA, C18, CarbonX, and MgSO 4 was used in this study. PSA is widely applied in the QuEChERS method to remove polar interferents such as sugars and organic acids from the matrix .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a recent report showed that an aqueous extract of Sarcodon imbricatus (SIE) effectively inhibited the growth, migration, and invasion properties of breast cancer cells in vitro and reduced tumor growth in vivo, while showing increased expression of PD-L1 and increased NK cell viability [152]. Furthermore, Xue et al reported that a triterpenoid EAe from Pleurotus eryngii inhibited MCF-7 cell lines proliferation with an EC50 of 298.26 µg/mL, and significantly inhibited the growth of CD-1 tumors (inhibition rate of 65%) in mice in a dose-dependent manner without toxicity [153].…”
Section: Mechanisms For the Immunomodulation Effects Of Medicinal Musmentioning
confidence: 99%